2021
DOI: 10.3389/fnins.2020.580929
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Metabolites in Acute Ischemic Stroke and Its Subtypes

Abstract: Existing techniques have many limitations in the diagnosis and classification of ischemic stroke (IS). Considering this, we used metabolomics to screen for potential biomarkers of IS and its subtypes and to explore the underlying related pathophysiological mechanisms. Serum samples from 99 patients with acute ischemic stroke (AIS) [the AIS subtypes included 49 patients with large artery atherosclerosis (LAA) and 50 patients with small artery occlusion (SAO)] and 50 matched healthy controls (HCs) were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…The most GO biological process enriched is the glycerolipid metabolic process. Wang et al (2021) has proved that the glycerophospholipid metabolism plays a role in IS. KEGG analysis revealed the importance of potassium transport channels in IS, and this also was demonstrated in the work of Chen et al (2016) , where they found that potassium channels can be a potential pharmacological target for IS to slow down cerebral edema formation.…”
Section: Resultsmentioning
confidence: 99%
“…The most GO biological process enriched is the glycerolipid metabolic process. Wang et al (2021) has proved that the glycerophospholipid metabolism plays a role in IS. KEGG analysis revealed the importance of potassium transport channels in IS, and this also was demonstrated in the work of Chen et al (2016) , where they found that potassium channels can be a potential pharmacological target for IS to slow down cerebral edema formation.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have investigated different metabolites in stroke [26,28,32,33]. Findings reveal new metabolites pathways for ischemic stroke subtypes and provide a new avenue to explore the pathophysiological mechanisms underlying ischemic stroke and its subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the underlying metabolic differences might lead to concrete starting points for a future research to improve care for men and women AIS patients. Existing studies [13,14,[26][27][28][29][30][31][32][33][34] that investigated metabolites in stroke focused on differences between stroke and control, hemorrhagic strokes compared with non-hemorrhagic or ischemic strokes. For example, elevated plasma DNA concentrations were detected in patients with hemorrhagic strokes compared with non-hemorrhagic strokes, with a 31% sensitivity and 83% specificity for discriminating the two types of stroke [34].…”
Section: Introductionmentioning
confidence: 99%
“…Among the biochemical mechanisms implicated in the pathophysiology of TBI, the inflammatory processes [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], and the impairment of the phospholipid metabolism and its consequences [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] play an important role. Because of these pathophysiological conditions, there is agreement on the need for drugs that may have a protective and restorative or reparative effect on the nervous system [ 36 , 37 , 38 , 39 , 40 ], the so-called “traumatic penumbra” being the target of their effect [ 22 ].…”
Section: Introductionmentioning
confidence: 99%